Basic research Neural differentiation of periodontal ligament stem cells induced by neurotrophic Schwann cells factors - Li, Xiaojie; Liao, Dapeng; Gong, Ping; Tang, Hua (Archives of Medical Science, 2009)
Introduction: Recent reports showed allogenic neurotrophic Schwann-cell factors could induce neural differentiation of mesenchymal stem cells, so we want to investigate whether heterogeneic neurotrophic Schwann-cell factors could induce neural differentiation of periodontal ligament stem cells (PDLSCs). Material and methods: We isolated and multiplied PDLSCs from periodontal ligament of 8 month old beagle dogs’ teeth (n = 24), and harvested Schwann cells from sciatic nerves of 1- to 2-day-old Sprague-Dawley rat pups, performing indirect co-culture of heterogeneic Schwann cells and PDLSCs with trans-well culture dishes. At 1, 3, 7 and 14 day after co-culture, Quantitative Real-time PCR and immunochemistry were performed to investigate the neural differentiation of PDLSCs. Results: Quantitative real-time PCR analysis disclosed the regularity of above differentiation: the mRNA expression level of S100 kept climbing from the 1st to the 14th day with a relative stable period from the 3rd to the 7th day; the mRNA expression level of Nestin continually decreased from the 1st to the 14th day with a relative stable period from the 3rd to the 7th day; the mRNA expression level of GFAP climbed from the 1st to the 3rd day, then maintained stable till the 14th day. Immunostaining results further confirmed the neural differentiation of PDLSCs from the protein level. Conclusions: PDLSCs could be induced to differentiate into a Schwann cell phenotype by indirect co-culture with heterogeneic Schwann cells, such neural differentiation began as early as 24 h after co-culture, but the most apparent neural differentiation of PDLSCs appeared 14 days later.